Gender Imbalance in Teaching Profession and Learning Outcome in Mathematics in Primary Schools in Esan West Local Government Area of Edo State - Olusi Felix Ilori (Randwick International of Education and Linguistics Science Journal, 2021)
The study assessed the imbalances in teaching profession in both public and private Nursery and Primary Schools, Public Secondary schools in Esan West Local Government Area of Edo State to determine the percentage/ ratio of imbalance and its relationship to learning outcome in mathematics at the primary school level. The study employed the descriptive survey research design. The population of the study comprised of all the seventy public and private Nursery and Primary Schools and thirty two public Secondary Schools with six hundred and sixty teachers in Esan West Local Government Area of Edo State. The data generated were analysed using the chi-square statistics. The findings from the study revealed that there was significant gender imbalance in teaching profession in Esan West Local Government Area of Edo State. The worst hit is the public nursery and primary school with an imbalance percentage of 78.87% and 21.13% in favour of female teachers while the private schools have a percentage imbalance of 76.02% and 23.98% in favour of female teachers. The female pupils’ performance in mathematics was better than that of the male pupils. The study revealed that at the secondary school the imbalance was significant at the junior secondary school level and milled at the senior secondary. The study recommended the immediate reversal of the trend of imbalance by employing more male teachers into the public and private nursery and primary schools. This will improve the academic achievement of male pupils in mathematics, hence achieving the best practice in Nigeria education.